Guillain-Barré Syndrome in Suriname; Clinical Presentation and Identification of Preceding Infections - Langerak, Thomas; van Rooij, Irene; Doornekamp, Laura; Chandler, Felicity; Baptista, Mark; Yang, Harvey; Koopmans, Marion P. G.; GeurtsvanKessel, Corine H.; Jacobs, Bart C.; Rockx, Barry; Adriani, Kirsten; van Gorp, Eric C. M. (Frontiers in Neurology, 2021)
Guillain-Barré syndrome (GBS) is associated with various types of preceding infections including Campylobacter jejuni and cytomegalovirus, but there is also an association with arthropod borne viruses (arboviruses), such as Zika virus, that are endemic in tropical regions. Here we present the clinical characteristics of 12 GBS patients from Suriname that were hospitalized between the beginning of 2016 and half 2018. Extensive diagnostic testing was performed for pathogens that are commonly associated with GBS, but also for arboviruses, in order to identify the preceding infection that might have led to GBS. With this extensive testing algorithm, we could identify a recent infection in six patients of which four of them had evidence of a recent Zika virus or dengue virus infection. These results suggest that arboviruses, specifically Zika virus but possibly also dengue virus, might be important causative agents of GBS in Suriname. Furthermore, we found that more accessibility of intravenous immunoglobulins or plasma exchange could improve the treatment of GBS in Suriname.